Electric motors and drives : fundamentals, types and applications - Hughes, Austin; Drury, Bill (Newnes, 2013)
Electric Motors and Drives is intended for non-specialist users of electric motors and drives, filling the gap between maths- and theory-based academic textbooks and the more prosaic 'handbooks', which provide useful detail but little opportunity for the development of real insight and understanding. The book explores all of the widely-used modern types of motor and drive, including conventional and brushless D.C., induction motors and servo drives, providing readers with the knowledge to select the right technology for a given job. The third edition includes additional diagrams and worked examples throughout. New topics include digital interfacing and control of drives, direct torque control of induction motors and current-fed operation in DC drives. The material on brushless servomotors has also been expanded. Austin Hughes' approach, using a minimum of maths, has established Electric Motors and Drives as a leading guide for electrical engineers and mechanical engineers, and the key to a complex subject for a wider readership, including technicians, managers and students. * Acquire knowledge of and understanding of the capabilities and limitations of motors and drives without struggling through unnecessary maths and theory * Updated material on the latest and most widely-used modern motors and drives, including brushless servomotors * New edition includes additional diagrams and worked examples throughout.
Keywords: Electric motors.; Electric driving.; elektronické knihy; electronic books